Maternal immunity shapes biomarkers of germinal center development in HIV‐exposed uninfected infants - Yin, Li; Venturi, Guglielmo M.; Barfield, Richard; Fischer, Bernard M.; Kim-Chang, Julie J.; Chan, Cliburn; De Paris, Kristina; Goodenow, Maureen M.; Sleasman, John W. (Frontiers in Immunology, 2024)
Introduction. HIV-exposed uninfected (HEU) infants exhibit elevated pro-inflammatory biomarkers that persist after birth. However, comprehensive assessments of bioprofiles associated with immune regulation and development in pregnant women with HIV (PWH) and HEU infants has not been performed. Maternal immunity in PWH may be imprinted on their HEU newborns, altering immune bioprofiles during early immune development.. Cryopreserved paired plasma samples from 46 HEU infants and their mothers enrolled in PACTG 316, a clinical trial to prevent perinatal HIV-1 transmission were analyzed. PWH received antiretrovirals (ARV) and had either fully suppressed or unsuppressed viral replication. Maternal blood samples obtained during labor and infant samples at birth and 6 months were measured for 21 biomarkers associated with germinal centers (GC), macrophage activation, T-cell activation, interferon gamma (IFNγ)-inducible chemokines, and immune regulatory cytokines using Mesoscale assays.Pregnant women without HIV (PWOH) and their HIV unexposed uninfected (HUU) newborns and non-pregnant women without HIV (NPWOH) served as reference groups.Linear regression analysis fitted for comparison among groups and adjusted for covariant(s) along with principal component analysis performed to assess differences among groups.Results: Compared with NPWOH, PWOH displayed higher levels of GC, macrophage, and regulatory biomarkers. PWH compared to PWOH displayed elevated GC, T cell activation, and IFN-γ-inducible chemokines biomarkers at delivery. Similar to their mothers, HEU infants had elevated GC, macrophage, and IFN-γ-inducible chemokines, as well as elevated anti-inflammatory cytokines, IL-10 and IL-1RA. Across all mother/newborn dyads, multiple biomarkers positively correlated, providing further evidence that maternal inflammation imprints on newborn bioprofiles. By 6 months, many HEU biomarkers normalized to levels similar to HUU infants, but some GC and inflammatory biomarkers remained perturbed. Bioprofiles in PWH and HEU infants were similar regardless of the extent of maternal viral suppression by ARV.Conclusions: GC immune pathways are perturbed in HEU newborns, but immune regulatory responses down regulate inflammation during early infancy, indicating a transient inflammatory effect. However, several GC biomarkers that may alter immune development remain perturbed.